2016
DOI: 10.3390/ijms17050766
|View full text |Cite
|
Sign up to set email alerts
|

An Eco-Friendly Ultrasound-Assisted Synthesis of Novel Fluorinated Pyridinium Salts-Based Hydrazones and Antimicrobial and Antitumor Screening

Abstract: The present work reports an efficient synthesis of fluorinated pyridinium salts-based hydrazones under both conventional and eco-friendly ultrasound procedures. The synthetic approach first involves the preparation of halogenated pyridinium salts through the condensation of isonicotinic acid hydrazide (1) with p-fluorobenzaldehyde (2) followed by the nucleophilic alkylation of the resulting N-(4-fluorobenzylidene)isonicotinohydrazide (3) with a different alkyl iodide. The iodide counteranion of 5–10 was subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…More specifically, pyridinium salts carrying long alkyl chains were found to be outstanding bioactive agents as antimicrobial [13], anticancer [14] and biodegradable [15] agents. Recently, we have reported a green ultrasound synthesis of novel fluorinated pyridinium hydrazones using a series of alkyl halides ranging from C2 to C7 [16]. The biological screening results revealed that the activity increased with increasing the length of the alkyl side chains, especially for hydrazones tethering fluorinated counteranions (PF 6 − , BF 4 − and CF 3 COO − ).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, pyridinium salts carrying long alkyl chains were found to be outstanding bioactive agents as antimicrobial [13], anticancer [14] and biodegradable [15] agents. Recently, we have reported a green ultrasound synthesis of novel fluorinated pyridinium hydrazones using a series of alkyl halides ranging from C2 to C7 [16]. The biological screening results revealed that the activity increased with increasing the length of the alkyl side chains, especially for hydrazones tethering fluorinated counteranions (PF 6 − , BF 4 − and CF 3 COO − ).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting 1,2,3-triazoles bearing bis-Schiff base moieties 5a – g were prepared in 87–90% yields. The 1 H-NMR spectra of similar reported compounds showed the existence of E/Zgeometrical isomers in the imine (CH=N) bond and cis/trans conformers in the amide (C=O and N–H) group [ 30 , 31 , 32 ] ( Scheme 2 ).…”
Section: Resultsmentioning
confidence: 93%
“…Based on interesting results published recently, we focused on the preparation of a new family of RTILs (1-20) by using microwave irradiation and conventional procedure in order to test them for antitumor activities [37][38][39]. As shown in Scheme 1, 1propylimidazolium-based ionic liquids (1-5) have been synthesized through the reaction of 1-propylimidazole in toluene with a suitable alkyl bromide at 80°C for 18 h. The quaternization reaction was performed via the nucleophilic attack of the Sp 2 -N imidazole atom on the alkyl bromide in order to produce the desired imidazolium bromides (1-5).…”
Section: Synthesismentioning
confidence: 99%